Editorial: New Research on Soil Degradation and Restoration. (1st September 2020) - Núñez-Delgado, Avelino; Zhou, Yaoyu; Anastopoulos, Ioannis; Shaaban, Muhammad
Abstract: The Virtual Special Issue (VSI) "New Research on Soil Degradation and Restoration" was proposed by the Guest-Editors (the authors of this editorial piece) to Journal of Environmental Management taking into account the following aspects: (a) Firstly, soil degradation is a main issue all over the world; (b) Secondly, physical, chemical and biological degradation of soil environments need detailed research, also going deeper in some new aspects poorly covered up to now; and (c) Similarly, new quality research on restoration of degraded soils, dumping sites, different areas affected by mining activities, and so on, would be clearly useful in order to prevent and/or solve critical environmental hazards. As a result, 110 manuscripts were submitted to the VSI by authors from around the world, and near 50 high quality works were finally published. The Guest-Editors of the VSI consider that the papers published will be of great interest for researchers working in this field, as well as for the overall community, as they include aspects clearly relevant at a global level.